Investigation of chirality in the case of 102Rh. (June 2016) - Yavahchova, M. S.; Tonev, D.; Goutev, N.; de Angelis, G.; Petkov, P.; Bhowmik, R.K.; Singh, R.P.; Muralithar, S.; Madhavan, N.; Kumar, R.; Kumar Raju, M.; Kaur, J.; et al.
Abstract: Excited states in 102 Rh were populated in the fusion-evaporation reaction 94 Zr( 11 B, 3n) 102 Rh at a beam energy of 36 MeV using the INGA spectrometer at IUAC, New Delhi. The angular correlations and the electromagnetic character of some of the gamma-ray transitions observed were investigated in details. A new chiral candidate sister band was found. Lifetimes of exited states in 102 Rh were measured using the Doppler-shift attenuation technique and the derived reduced transition probabilities are compared to the predictions of the Two Quasiparticles Plus Triaxial Rotor model.